Primary cortisol resistance in man. A glucocorticoid receptor-mediated disease. - Chrousos, G P (1982)
We have studied a man suspected of having primary cortisol resistance on the basis of high 24-h mean plasma cortisol levels (27.4 micrograms/dl) and no stigmata of Cushing's syndrome. His son had slightly elevated 24-h mean plasma cortisol levels (9.9 micrograms/dl; normal 7.52 micrograms/dl). Both had high plasma protein unbound cortisol and increased urinary free cortisol. Plasma ACTH concentration was high, and both were resistant to adrenal suppression by dexamethasone. The father appeared to have mineralocorticoid excess resulting in hypertension, hypokalemia, and metabolic alkalosis. This was found to be due to markedly elevated plasma levels of deoxycorticosterone and corticosterone. The son, who was normotensive, had mildly increased plasma corticosterone and normal deoxycorticosterone levels. To study the apparent end-organ resistance to cortisol, we examined the glucocorticoid receptor in the white cells and fibroblasts of these patients. In both tissues, using both whole cell and cytosol assays, the glucocorticoid receptor was found to have reduced affinity for dexamethasone. In the cytoxol assays, a reduced receptor number was found as well. We conclude that cortisol resistance is a rare familial syndrome owing to an abnormal glucocorticoid receptor with a decreased affinity for cortisol.